Presença de anormalidades anatômicas na eminência arqueada do osso temporal: um estudo em cadáveres - Moura, Kelvin (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
ABSTRACT Introduction: the arcuate eminence (AS) is an important anatomical repair to demarcate the location of the superior semicircular canal (SSC) during surgeries with access through the middle cranial fossa. However, its use has been questioned in the literature due to its varied presentation and questionable relationship with CSS. Objective: to elucidate the topography of the arcuate eminence and observe the presence of anatomical changes and/or variations in this structure. Methodology: this is a cross-sectional study developed from the open dissection of adult cadaver heads. All anatomical measurements were performed with the aid of a digital carbon fiber caliper with an accuracy of 0.1 mm. Results: the study consisted of the analysis of 40 antimeres from 20 specimens. It was possible to identify EA in 92.5% of these pieces and no CSS dehiscence was observed in any of the pieces studied. The distance from EA to cranial vault was on average 25.66mm with a standard deviation of ± 4.6; from the EA to the internal carotid arteries was 47.12mm with a standard deviation of ± 4.2 and from the EA to the internal auditory canal the distance was 18.23mm, with a standard deviation of ± 2.6. Conclusion: EA is a structure with varied presentation, such that an individualized and detailed preoperative study is necessary for a correct and safe surgical technique. CSS dehiscence is a rare variation that requires local studies on its prevalence.